Investigating the program format of Pulso ng Bayan - Peconada, Joy D.
The study focused on the content of the radio program, Pulso ng Bayan in order to identify its program format. The study emphasized detailed content analysis of a limited segments of the program Pulso ng Bayan, thus the study specially used the qualitative and quantitative data gathering. The researcher recorded 10 airing times of the program. The recordings were done from October 10 to October 11, October 16 to October 18, and October 22 to October 26, 2012. After the recording, the data was transcribed and analyzed through tabulating and obtaining the frequency of each variables and elements. After obtaining the frequency, the results were analyzed by working each element and each variable being presented. Based on the results and analysis of the researcher, Pulso ng Bayan applied triformat. The program make use of three different format in one program, and that?s make Pulso ng Bayan unique from any other public affairs program. The researcher also found out that the format applied in the program are not exclusive for the two hour program, it was also applied on the activities that was created and done by the station to extend the public service offered by the program. Pulso ng Bayan is public service oriented that includes the participation of the audience in the radio commentary program.